Community Empowerment In Producing Catfish Food Using Maggot With Palm Solid Waste Media Efforts Of Post Covid-19 Pandemic Economic Recovery : Pemberdayaan Masyarakat Dalam Pembuatan Pakan Ikan Lele Menggunakan Maggot Dengan Media Limbah Solid Kelapa Sawit Upaya Pemulihan Perekonomian Pasca Pandemi Covid-19 - Retno, Ria; Sirait, Debora Exaudi; Siagian, Gunaria (Yayasan Ahmar Cendekia Indonesia, 2023)
The Covid-19 pandemic has caused an economic crisis, the price of feed is increasing so that the selling price of catfish no longer matches the price of the feed provided. The focus of community service in the Tanjung Kasau Plantation village is to assist fish farmers in managing and increasing fish farmers' income. The priority objective of this activity is efforts to improve the economy, namely increasing income in terms of production costs, both fish feed, production cost management and training in maggot cultivation by utilizing surrounding waste, namely solid palm oil waste. The implementation method is carried out in 3 stages which involve problems in the fields of production and management. This service activity uses education, training and mentoring methods. Community-Based Empowerment Activities carried out at the Tangkas Mina Jaya Group in Tanjung Kasau Plantation Village ran smoothly, marked by good community participation from the start to the end of the activity. Community-Based Empowerment Activities also provide a positive impact by increasing community knowledge and skills